Endoscopic entero-enteral bypass to treat postsurgical benign complications of hepatico-jejunostomy: Update of a 7-year single-center experience - Massimiliano Mutignani; Edoardo Forti; Francesco Pugliese; Marcello Cintolo; Giulia Bonato; Marianna Bravo; Lorenzo Dioscoridi (Endoscopy International Open, 2023)
Background and study aims Since 2014, we have been using a new endoscopic approach to improve management of biliary adverse events (BAEs) after bilio-digestive anastomosis. We provide an update about our experience at 7 years. Patients and methods Patients with BAEs on hepatico-jejunostomy underwent entero-enteral endoscopic by-pass (EEEB) creation between the duodenal/gastric wall and the biliary jejunal loop. Evaluation of results during our seven-year experience was performed. Results Eighty consecutive patients (32 patients from Jan 2014 to Dec 2017 and 48 patients from Jan 2018 to Jan 2021) underwent EEEB, which was successful in all but one patient. The cumulative AEs rate was 32 %. Endoscopic retrograde cholangiography (ERC) through the EEEB successfully treated all types of BAEs in these patients. Cumulative disease recurrence was 3.8 % (three patients) and was retreated through the EEEB. Conclusions The update of our experience with EEEB confirmed that in patients with BAEs after bilio-digestive anastomosis, EEEB allows successful long-term treatment of different BAEs in a tertiary referral center with an acceptable rate of related AEs.